2006
DOI: 10.1038/modpathol.3800562
|View full text |Cite
|
Sign up to set email alerts
|

Study of phospho-β-catenin subcellular distribution in invasive breast carcinomas in relation to their phenotype and the clinical outcome

Abstract: b-Catenin has a crucial role in cell-cell adhesion as well as a signaling role as a member of the Wnt pathway. The aim of this study was to examine the clinicopathological and prognostic value of phosphorylated b-catenin, as well as its relation to the tumors' phenotype, in breast cancer. Immunohistochemistry was applied on 141 paraffin-embedded breast tissue specimens for the detection of phospho-b-catenin, ER, PR, c-erbB-2, p53, Ki-67, bcl-2, uPAR and TIMP-1. For each case, a phospho-b-catenin index was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 27 publications
1
52
1
1
Order By: Relevance
“…Some studies have shown that phosphorylated β-catenin was immunodetected in both the cytoplasm and nuclei of cancer cells (21) and that phosphorylated β-catenin expression was localized almost exclusively in the nuclei in cancers, such as melanoma and colorectal cancer (20,40). Nuclear localization of phosphorylated β-catenin may be related to changes at other stages in the signaling pathway (20)(21)(22)(23)40). A high level of nuclear phosphorylated β-catenin was involved in the increased invasiveness phenotype and in the low survival rates of melanoma and breast cancer (20,21).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies have shown that phosphorylated β-catenin was immunodetected in both the cytoplasm and nuclei of cancer cells (21) and that phosphorylated β-catenin expression was localized almost exclusively in the nuclei in cancers, such as melanoma and colorectal cancer (20,40). Nuclear localization of phosphorylated β-catenin may be related to changes at other stages in the signaling pathway (20)(21)(22)(23)40). A high level of nuclear phosphorylated β-catenin was involved in the increased invasiveness phenotype and in the low survival rates of melanoma and breast cancer (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…A high level of nuclear phosphorylated β-catenin was involved in the increased invasiveness phenotype and in the low survival rates of melanoma and breast cancer (20,21). Because nuclear phosphorylated β-catenin was implicated in the aggressiveness and invasiveness of tumor cells through its positive correlation with invasiveness and antiapoptotic molecules, uPAR, bcl-2, and TIMP-1, nuclear phosphorylated β-catenin may be a more sensitive probe for biologically significant activation of tumor cells (21)(22)(23). The current study suggests that Dkk1 regulates phosphorylated β-catenin level in nuclei, which would be correlated with the migration and invasiveness of OSCC cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alteration of molecular biological markers in tumor tissues has become an important part in predicting the prognosis of patients with BC and seemed more specific than markers currently used in clinical such as TNM stage, weight loss and lymph node metastasis. There are many reports about the prognostic significance of β-catenin in BC (Lin et al, 2000;Gillett et al, 2001;Lim and Lee, 2002;Chung et al, 2004;Dolled-Filhart et al, 2006;Nakopoulou et al, 2006;Park et al, 2007;Fanelli et al, 2008;Paredes et al, 2008;Khramtsov et al, 2010;Kim et al, 2010;Logullo et al, 2010;Lopez-Knowles et al, 2010;Geyer et al, 2011;Cheng et al, 2012;Mukherjee et al, 2012;Xu et al, 2012;Ho et al, 2013;Pang et al, 2013;Weissenbacher et al, 2013;Li et al, 2014). However, results were inconsistent.…”
Section: Sensitivity Analysismentioning
confidence: 99%